PENINGKATAN HASIL BELAJAR GERAK MOTORIK MENGGUNAKAN METODE BERMAIN PESERTA DIDIK KELAS 1 SDN SAWUNGGALING VIII/ 389 KOTA SURABAYA - Purwaningtyas Purwaningtyas; Abdul Rachman Syam Tuasikal; Moedajanah Moedajanah (STKIP PGRI Jombang, 2023)
Physical Education is an important component of a well-rounded education. Physical Education involves the development of physical fitness, motor movement skills, and social skills through physical fitness activities. Physical Education as an integral part of education has a role in the learning done by students to be in accordance with teaching at the right level. In its application, it is treated with the play method. Elementary school age has an important aspect that must be stimulated in addition to cognitive and affective is the psychomotor (learning) motor of students. The first step to support ideal growth and development by providing stimulation to children's motor movements. This study aims to improve the learning outcomes of motor movements with the play method for grade 1 students of SDN Sawunggaling 8 Surabaya. Researchers used the Classroom Action Research method with a total of 32 students. The results of this study conducted from cycle I to cycle III experienced a significant increase in learning outcomes, in cycle I (48.54%), cycle II (59.58%) and cycle III (76.74%).